2015
DOI: 10.1021/acs.inorgchem.5b00462
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction, Mössbauer Spectroscopy, Magnetic Susceptibility, and Specific Heat Investigations of Na4NpO5 and Na5NpO6

Abstract: The hexavalent and heptavalent sodium neptunate compounds Na4NpO5 and Na5NpO6 have been investigated using X-ray powder diffraction, Mössbauer spectroscopy, magnetic susceptibility, and specific heat measurements. Na4NpO5 has tetragonal symmetry in the space group I4/m, while Na5NpO6 adopts a monoclinic unit cell in the space group C2/m. Both structures have been refined for the first time using the Rietveld method. The valence states of neptunium in these two compounds, i.e., Np(VI) and Np(VII), respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The Na 4 AnO 5 (An = U, Np, Pu) composition is common to all three systems with a tetragonal structure, in space group I4/ m. 9,29,30 Heptavalent Na 5 NpO 6 and Na 5 PuO 6 are both monoclinic, in space group C2/m. 19,30 All of these ternary oxide phases show 6-fold-coordinated actinide cations as described in detail in the following sections. Moreover, the mean U−O, Np−O, and Pu−O distances in the AnO 6 octahedra decrease when the valence state of the actinide cation increases, which is expected from the size of the respective ionic radii, as reported in ref 26.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Na 4 AnO 5 (An = U, Np, Pu) composition is common to all three systems with a tetragonal structure, in space group I4/ m. 9,29,30 Heptavalent Na 5 NpO 6 and Na 5 PuO 6 are both monoclinic, in space group C2/m. 19,30 All of these ternary oxide phases show 6-fold-coordinated actinide cations as described in detail in the following sections. Moreover, the mean U−O, Np−O, and Pu−O distances in the AnO 6 octahedra decrease when the valence state of the actinide cation increases, which is expected from the size of the respective ionic radii, as reported in ref 26.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Keller and coworkers pioneered the study of the interaction between minor actinides (Np, Am) and alkali metals. 8,9 As part of our program of research, we have recently revisited the structural properties of the Na-Np-O 10,11 and Na-Pu-O systems, 12 and confirmed the formation of the hexavalent and heptavalent compounds Na 2 NpO 4 , Na 4 AnO 5 , Na 2 An 2 O 7 , and Na 5 AnO 6 (An = Np, Pu). The present study focuses on the pentavalent composition Na 3 AnO 4 , as this product is more likely to form under the oxygen potential conditions of the reactor.…”
Section: Introductionmentioning
confidence: 92%
“…The XANES spectrum of K 2 NpO 4 collected at the Np-L 3 edge is shown in Figure together with those of NpO 2 , Na 3 Np V O 4 , α-Na 2 Np VI O 4 , Na 4 Np VI O 5 , and Na 5 Np VII O 6 reference materials . The valence states of the sodium neptunates were confirmed by 237 Np Mössbauer spectroscopy from the values of their isomer shifts, while the corresponding XANES spectra were reported in ref . The values of the measured inflection points and white lines are reported in Table .…”
Section: Results and Discussionmentioning
confidence: 85%
“…47 Those studies have revealed intriguing magnetic properties for the α-Na 2 Np VI O 4 7 and Na 4 Np VI O 5 6 compositions and have stressed the need to re-evaluate the Np(VI) crystal-field ground state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation